Ranking performances of Olympic-style weightlifters adjusted for body mass on the same scale for both sexes: A novel approach - Huebner, M.; Cole, T. J. (Journal of Sports Sciences, 2024)
Males typically outperform females in Olympic-style weightlifting, as judged by total weight lifted, and similarly heavier athletes outperform lighter athletes. Current methods can standardise weightlifting performances across body mass to compare different body mass classes, but they do not address the sex gap. This study introduces a novel approach that puts male and female performances on a single unified scale, across the range of body mass, allowing mixed sex teams to be compared. The method uses standardised residuals or "z-scores" derived from models of performance regressed on sex and body mass fitted by GAMLSS (generalised additive models for location, scale and shape). Reference data come from the International Weightlifting Federation (IWF) world championships and Olympics 2017-2023. To ensure the validity of the model for ranking team performances in the future, results from 2000 to 2023 were compared and shown to be stable over time. A web application is available to aid athletes, coaches and health professionals to compare performances and monitor progress over time.